Flexural Strength of Composite Based Provisional Crown Materials - Osama Qutub,; Salman Khalid Bashnani,; Faisal Khalid Bashnaini, (International Journal of Innovative Research in Medical Science, 2021)
Introduction: One of the important aspects of provisional restorations, especially in case of long-span edentulous situations, short-height pontics, extended treatment time and in patients with para-functional habits is their flexural strength. Maintaining the integrity of the provisional restorations throughout the course of treatments is highly valuable and important to have a predictable outcome. Objectives: To evaluate and compare the flexural strength of composite based provisional materials. Materials and Methods: Materials: Group 1, conventional bisacryl composite material (Protemp 4, 3M). Group 2, Computer Assisted Designing - Computer Assisted Milling (CAD-CAM) composite provisional material (CAD Temp). Method: Twenty identical specimens sized 25×2×2-mm were prepared from each material. A standard three-point bending test was conducted on the specimens with a universal testing machine at a 0.5 mm/min crosshead speed, and the flexural strength values were calculated (MPa) for each specimen. The flexural strength data were statistically analyzed using T-Test. Results: The measured mean flexural strength values (MPa) were as follow: group1 = 99.38 in comparison to group 2 = 92.06. There were statistically significant differences among the flexural strengths of tested materials (P < 0.05), The conventional group had significantly higher flexural strength than the CAD/CAM group (p < 0.05). Conclusion: Within the limitation of this study, the bisacryl composite resin (Protemp 4) provisional material has superior flexural strength than CAD/CAM composite material. Although many authors recommended the use of CAD/CAM provisional materials, this study prove that the material composition is as important as the material method of fabrication.